EMPLOYEE ENGAGEMENT IN THE WORKPLACE: A SYSTEMATIC LITERATURE REVIEW - Lilia Demupa; Yunita Faela Nisa; Abdul Mujib (RADJA PUBLIKA, 2026)
This study aims to map empirical findings on employee engagement as a dependent variable in workplace contexts using a Systematic Literature Review (SLR) approach. Literature searches were conducted across three academic databases: Google Scholar, ScienceDirect, and Garuda Ristekdikti, covering publications from 2020 to 2025. Article selection followed PRISMA guidelines, with inclusion criteria comprising quantitative studies, workplace-focused contexts, employee engagement as the dependent variable, and full-text accessibility in Indonesian or English. Out of 395,874 identified records, 24 articles met all inclusion criteria and were further analyzed. Findings were synthesized using meta-analytic techniques where applicable and complemented by narrative synthesis to interpret heterogeneous results. The review indicates that organizational factors such as leadership styles, human resource management practices, perceived organizational support, quality of work life, and workplace environment have a significant effect on employee engagement. Individual and contextual factors, including workplace spirituality and employee well-being, also have an effect on enhancing engagement. This review highlights research gaps, particularly the limited evidence from Indonesian MSMEs and the underexplored role of several predictors, thereby offering directions for future research.